THE APPLICATION OF THE LAW OF THE IMPOSITION OF THE BEA ACQUISITION OF RIGHTS TO LAND AND BUILDINGS (BPHTB) - Marlon Gustia (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
The research about tax, especially about acquisition tax of land and buildings (BHTP) very important because this is financing part from society to development our state This research tried to analyzing a few legal problems, such as:  legal basis registration of lands, requirements and mechanisms BHTP based on Law of The Republic Indonesia Number 28 of 2009 concerning Local Taxation and Charges, BHTP collection policy for land registration in Central Lombok Regency This research used Normative method and empirical method namely: conceptual approach, statute approach, cases study, the results is land as part from the earth had social function, and its has potential investment for every person who have rights on land and building, they have duty to give economic value to their states through tax payment, in this case through  imposition excise on acquired right on land and building (BPHTB)  Keyword: Land Registration, BHTP tax